Haptic Tests for Use with Children and Adults with Visual Impairments: A Literature Review. (May 2014) - Mazella, Anaïs; Albaret, Jean-Michel; Picard, Delphine
We sought to provide a quantitative overview of haptic tests, so as to identify what has been done in this area so far and discuss possible avenues for the future design of haptic tests for use with persons with visual impairments. We reviewed 24 haptic psychometric tests, that is, tests performed in the haptic modality, with no reliance on vision. We found that haptics (that is, tactilokinesthetic perception or the sense of active touch) has been used in two different ways: first, to assess nonverbal or practical intelligence, replacing vision in haptic analogs of mainstream tests (for example, tactile adaptations of Wechsler performance scales); second, to assess, per se, the quality of haptic functioning in specialized tests (for example, Tactual Profile, Haptic Test Battery). In both cases, we found that only a limited number of tests had been standardized for children or were developmental tests or both. We also noticed an overwhelming use of 3-D material in the tests, and a general lack of a comparison group (blindfolded sighted participants) during the standardization process. We discuss the usefulness of designing developmental haptic test batteries to assess 2-D haptic functioning in visually impaired and sighted children.